Micronutrient intakes and potential inadequacies of community-dwelling older adults: a systematic review. Issue 8 (30th March 2015) - ter Borg, Sovianne; Verlaan, Sjors; Hemsworth, Jaimie; Mijnarends, Donja M.; Schols, Jos M. G. A.; Luiking, Yvette C.; de Groot, Lisette C. P. G. M.
Abstract : Micronutrient deficiencies and low dietary intakes among community-dwelling older adults are associated with functional decline, frailty and difficulties with independent living. As such, studies that seek to understand the types and magnitude of potential dietary inadequacies might be beneficial for guiding future interventions. We carried out a systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Observational cohort and longitudinal studies presenting the habitual dietary intakes of older adults ( ≥ 65 years) were included. Sex-specific mean (and standard deviation) habitual micronutrient intakes were extracted from each article to calculate the percentage of older people who were at risk for inadequate micronutrient intakes using the estimated average requirement (EAR) cut-point method. The percentage at risk for inadequate micronutrient intakes from habitual dietary intakes was calculated for twenty micronutrients. A total of thirty-seven articles were included in the pooled systematic analysis. Of the twenty nutrients analysed, six were considered a possible public health concern: vitamin D, thiamin, riboflavin, Ca, Mg and Se. The extent to which these apparent inadequacies are relevant depends on dynamic factors, including absorption and utilisation, vitamin and mineral supplement use, dietary assessment methods and the selection of the reference value. In light of these considerations, the present review provides insight into the type and magnitude of vitamin and mineral inadequacies.